(untitled) (Latakia University Journal -Basic Sciences Series, 2017)
درست 11 عينة من الرمال الشاطئية لمنطقة جنوب طرطوس باتجاه شمال جنوب نقريبا وبمسافة حوالي 15 كم، تم تحديد 27 نوعا من هياكل المنخربات الموجودة فيها، أغلبها كان قاعيا مع سيطرة ملحوظة للهياكل البورسلانية. يزداد غنى هذه الرمال بهياكل المنخربات مع الاقتراب من خط الشاطئ، كما أن الرمال الناعمة البعيدة عن خط الشاطئ أقل غنى بهياكل المنخربات من الرمال الخشنة الأقرب إلى الشاطئ، وهذا يعود إلى فعل التجوية الذي يشارك فيها عمل الرياح بشكل فعال، حيث يتم تحطم وتكسر الهياكل نتيجة لذلك. إن مثل هذه العمليات الجيولوجية الحالية يمكن إسقاطها على الزمن الجيولوجي السابق لاسيما البليستوسين، حيث توضع الحجر الرملي بعمليات جيولوجية مشابهة لما يحدث في العصر الحالي. Eleven Samples of costal sand was studied, nearly south- north along 15 km ,27 Spcieses of Foraminifera Testes was determined (founded)in it, most of them was benthic , but the porcelanic testes were more commen. This Costal sand is richer in Foraminifera Testes near the costal line. As well as the fine far costal sand less richer in Foraminifera Testes than the coarse sand which is near of costal line, because of the effect of weathering , which the Aeolian processes very clear in it. And this causes brokig the Foraminifera Testes. The recent geological processes can be reflex at the past geological time, especially for sand stone in Pleistocene Age. This sandstone deposit by geological processes seemlywhat happing in our days ( recent).